RANCANG BANGUN AUTOFEEDER DENGAN PELONTAR BERBAHAN POLY VINIL CHLORIDE (PVC) UNTUK TAMBAK UDANG - A Marsha Alansar; Setyawan Dwi Nugroho; Rizqi Ilmal Yaqin (COJ (Coastal and Ocean Journal), 2020)
In aquaculture, mainly for shrimp farming, feeding is an important thing. Feeding manually with the hand is less effective and ineffective. Thus, an automatic feeder is needed to dispense food at a predetermined time. The advantages of automatic feeders are cost-effective, reduce labor requirements, and allow large volumes of feed to feed efficiently. Autofeeder is a modern fish feeder that can be used in several ponds. Therefore, in this research, the Autofeeder has been made with PVC pipe for the feed thrower. The test results show that the speed of the electric motor after loading is 2782 rpm. Meanwhile, the thrower maximum distance is 10 m.